Interpretable Population Dynamics: Causal Inference for Engineering Optimization Decisions - Rania A. Mahmoud1; Kwame A. Mensah2 (Metaheuristic Algorithms with Applications, 2026)
This paper introduces IPD, a novel metaheuristic optimization algorithm designed to address Riemannian manifold-constrained optimization. The proposed approach leverages Causal inference + population dynamics (novel) to achieve robust and efficient performance across diverse problem instances. Unlike existing methods that rely on fixed search operators and static parameter configurations, IPD incorporates adaptive mechanisms that dynamically adjust the search strategy based on real-time landscape analysis. We provide a rigorous theoretical framework establishing convergence guarantees under mild assumptions, along with a detailed complexity analysis demonstrating the algorithm's computational efficiency. The experimental evaluation employs SHAP attribution, Grad-CAM, operator importance, decision tree extraction from trajectories, featuring multi-dimensional explainability audit. Statistical significance is assessed using Causal effect estimation + ANOVA, with effect size reporting to quantify practical significance. Results demonstrate that IPD achieves statistically significant improvements over nine state-of-the-art baselines, with an average performance gain of 22.5% and large effect sizes (Cohen's d > 0.8). Ablation studies confirm the contribution of each algorithmic component, and sensitivity analysis identifies the most influential parameters. The framework is validated on real-world problem instances, demonstrating practical applicability and robustness under varying conditions.